Atypical spinal tuberculosis involved noncontiguous multiple segments: Case series report with literature review. Issue 14 (April 2017) - Wang, Lin-Nan; Wang, Lei; Liu, Li-Min; Song, Yue-Ming; Li, Yue; Liu, Hao
Abstract : Abstract: In its typical form, spinal tuberculosis (TB) presents as destroyed contiguous vertebral bodies with involvement of intervertebral discs and paravertebral or psoas abscesses. Atypical forms are uncommonly reported. Here, we describe 8 patients with noncontiguous multisegmental spinal TB with no intervertebral disc involvement. From 2013 to 2014, we surgically treated 384 patients with spinal TB to relieve spinal cord compression, re-establish spinal stability, confirm the diagnosis, and debride the TB foci. Eight of these patients had noncontiguous multisegmental TB without intervertebral disc involvement. Seven of the 8 patients underwent short-segmental fixation and fusion at a single focus. Appropriate combinations of anti-TB medication were continued until final follow-up. They were followed at established intervals using plain radiography, 3-dimensional computed tomography, and magnetic resonance imaging of the surgical region to evaluate fusion and the condition of the foci. Mean follow-up was 26.6 months (range, 24–32 months), during which time all patients were prescribed the appropriate anti-TB medications. Satisfactory clinical and radiological results were obtained in all patients, without complications. Presentation of noncontiguous multisegmental spinal TB without the involvement of intervertebral disc resembles that of a neoplasm or other spinal infection. Differentiation requires the presence of a combination of general symptoms, laboratory test results, appropriate radiological results, and the physician's experience. For patients in whom surgery is indicated, the patient's general condition should be taken into consideration. Surgical intervention only focus on the responsible level is less invasive and can achieve satisfactory clinical and radiographic outcomes.